KÜTAHYA YÖRESİ BAZI SİLVİKÜLTÜREL UYGULAMALARIN DEĞERLENDİRİLMESİ - Ertuğrul, Gülnur Saba; Bilir, Nebi (Bartın Üniversitesi, 2022)
Bu çalışmada, önemli silvikültürel faaliyetlerden olan, yanan orman alanlarının ağaçlandırılması, doğal gençleştirme ve normal ağaçlandırma uygulamaları, Kütahya Orman Bölge Müdürlüğü ölçeğinde, her bir uygulamadan örneklenen 1000 m2 büyüklüğündeki 3'er örnek saha verileri irdelenerek değerlendirilmiştir. Elde edilen bulgular ışığında, en yüksek ortalama fidan sayısına 266 fidanla gençleştirme sahalarının, ortalama en yüksek fidan boyuna (295.5 cm) gençleştirme sahalarının, ortalama en yüksek dip çapa ise normal ağaçlandırma sahalarının (8.5 cm) sahip olduğu ortaya çıkmıştır. Yangın ve normal ağaçlandırma sahaları yaş bakımından benzer (8.8 ve 8.9 yıl) değerlere sahipken, gençleştirme sahaları bunlardan daha yüksek (10.5 yıl) yaş değerine sahiptir. Uygulamalar ve uygulama içi alanlar, çalışmaya konu özellikler bakımından anlamlı (p<0.01) farklılıklar göstermiştir. Bu sonuçlar, ormancılık faaliyetlerinde yöresellik kanununun önemini vurgulamıştır. Duncan testi sonucunda boy, diğer özelliklere göre daha heterojen bir yapı göstermiştir. Çalışmaya konu özellikler arasındaki istatistiksel bakımdan anlamlı (p<0.01) pozitif ilişkiler belirlenmiştir. Elde edilen sonuçlar ışığında, bakım, yöntem seçimi gibi silvikültürel uygulamalara yönelik önerilerde bulunulmuştur.

Afforestation of forest fire area, natural regeneration and routine afforestation areas which were basic silvicultural practices were investigated based on Kutahya Forest District by three sampled areas which was each 1000 m2 of each practices by height, diameter, age and number of seedlings/reproductions to contribute forestry practices, in this study. Results of study showed that number of individuals (266) and average height (295.5 cm) were the highest in natural regeneration areas, while diameter at base was the highest (8.5 cm) in routine afforestation areas. Ages of forest fire area and routine afforestation areas were similar (8.8 and 8.9 years), while it was higher (10.5 years) in natural regeneration area. There were large differences among sampled areas within method for the characteristics. The variation could be because of mother tree or also called seed tree which were used in the practices. Significant differences (p<0.01) were found among forest fire, natural regeneration, and routine afforestation areas, and within practice among sampled areas by results of analysis of variance. The results emphasized importance of local forestry practices and regeneration methods. However, there could be many environmental and biological factors in the variation such as species, method, edaphic and age. Duncan's multiple range's test showed that height had the highest heterogeneous than other characteristics. It showed importance of height as a selection criterion for forestry practices to obtain higher quality and quantity forest products. Positive and significant (p<0.01) relations among the characteristics were estimated by results of phenotypic correlation analysis. The results could be used for early tending practices such as early and cultural stages. Some suggestions were given such as tending, method of silvicultural practices and for other practices based on results of the study. However, the present study had limited areas. New studies should be carried out in different regions and species, and also characteristics to give accurate conclusions for the forestry practices.
EVALUATION OF SOME SILVICULTURAL PRACTICES IN KUTAHYA DISTRICT
Keywords: Forest Industry Engineering; Orman Endüstri Mühendisliği